Sistema federativo à luz da jurisprudência do STF e do princípio da subsidiariedade - Sales, Fernando Coimbra Marques Farias Magalhães Bispo de (2023)
This dissertation aims to analyze the Brazilian federal system, both in its political aspect (legislative competencies) and fiscal aspect (taxing competence and revenue sharing), considering the jurisprudence of the Supreme Federal Court (STF) and the principles of subsidiarity and efficiency. This research investigates, in particular, twenty-two Direct Actions of Unconstitutionality (ADIs) whose judgments were published in the STF Informative magazine in the second half of 2022. The ADIs judged by the STF and analyzed in this dissertation notably cover subjects related to the legislative competence of federative entities regarding traffic and transportation, exploitation of deposits, ICMS (state tax on the circulation of merchandise and interstate and intercity transport and communication services), environmental law, telecommunications, consumer rights, tax system, etc. In order to achieve the proposed objective, this investigation adopts the deductive method, testing the validity of existing information concerning the federal system, constitutional control, the principle of subsidiarity, and so on. The information related to these and other highlighted topics was gathered through bibliographical research, including books, scientific articles, online articles, etc. Content analysis was employed in the ADIs to identify the stance of the STF in favor of the union (centralization) or subnational entities (decentralization) in the judgments related to the political and fiscal federal system. Therefore, based on this dissertation it is possible to observe that in the analyzed judgments, there is a tendency toward centralization in the STF's decisions in favor of the Union, and such a stance by the court in a cooperative federal system does not contribute to the strengthening of subnational entities. The federative system and the principle of efficiency was also analyzed based on the examination of some STF rulings on the subject. Finally, the principle of subsidiarity was studied for its history and its relationship with various topics in Political Science. This dissertation suggests that in cases of competence conflicts between federal entities, the principle of subsidiarity will provide the necessary support for the improvement towards decentralization and regionalization in decision-making regarding the Brazilian federal system.